2001
DOI: 10.1097/00005537-200110000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Improved Patient Outcomes With a Partially Implantable Hearing Aid, The SOUNDTEC Direct Hearing System

Abstract: Partially implantable hearing aids may address some of the limitations of traditional amplification systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 4 publications
(2 reference statements)
0
33
0
1
Order By: Relevance
“…The observational studies that mentioned the Hawthorne effect as an explanation for some of their outcomes were all good quality studies (Table ). Five RCTs were of poor quality, mainly due to personnel not being blinded to the intervention and one was of fair quality as shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The observational studies that mentioned the Hawthorne effect as an explanation for some of their outcomes were all good quality studies (Table ). Five RCTs were of poor quality, mainly due to personnel not being blinded to the intervention and one was of fair quality as shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, because the transducer directly drives the ossicles near the cochlea, signal degradation and distortion effects related to anatomical and physiological characteristics of the ear canal and tympanic membrane are reduced . Several studies have demonstrated that functional gain and speech recognition improvement with MEIs is equivalent to or better than optimally fitted hearing aids, whereas patient‐perceived outcome measures show that active MEIs provide superior sound quality, reduced occlusion and feedback, and improved patient satisfaction …”
Section: Introductionmentioning
confidence: 99%
“…More than 120 English language studies have been published in which researchers have used the APHAB as an assessment tool to measure the appropriateness and patterns of subjective performance for a variety of audiologic interventions. These interventions include hearing aid fitting procedures (e.g., Moore et al 2005;Gatehouse et al 2006;Shi et al 2007) and cochlear implant fitting strategies (e.g., Beynon et al 2003;Litovsky et al 2006;Gifford et al 2007) as well as methods of fitting nonconventional hearing aids such as middle ear implants, partially implantable hearing aids, and boneanchored hearing aids (e.g., Fraysse et al 2001;Roland et al 2001;Hol et al 2004). The APHAB also has been used to predict hearing aid use (e.g., Freyaldenhoven et al 2008) and for evaluating relationships between acceptable noise levels and subjective outcome measures for hearing aid and cochlear implant users (e.g., Saxon et al 2001;Freyaldenhoven et al 2008;Plyer et al 2008).…”
Section: Introductionmentioning
confidence: 99%